2016
DOI: 10.1007/s00415-016-8265-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based analysis of cortical thickness and structural connectivity in Parkinson’s disease

Abstract: Parkinson’s disease (PD) is a progressive neurological disorder and appears to have gender-specific symptoms. Studies have observed a higher frequency for development of PD in male than in female. In the current study, we evaluated the gender-based changes in cortical thickness and structural connectivity in PD patients. With informed consent, 64 PD (43 males and 21 females) patients, and 46 (12 males and 34 females) age-matched controls underwent clinical assessment including MiniMental State Examination (MMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 48 publications
(64 reference statements)
5
35
0
Order By: Relevance
“…For measuring the network difference between pediatric HIV patients and healthy controls, a non-parametric permutation test with 100 repetitions was performed. In each repetition, cortical and subcortical volumes (84 ROIs) were randomly reassigned to each individual from the two groups and association matrices were generated for each group ( Yadav et al, 2016 ). By thresholding the association matrices at a range of network densities, we estimated the binary adjacency matrices.…”
Section: Methodsmentioning
confidence: 99%
“…For measuring the network difference between pediatric HIV patients and healthy controls, a non-parametric permutation test with 100 repetitions was performed. In each repetition, cortical and subcortical volumes (84 ROIs) were randomly reassigned to each individual from the two groups and association matrices were generated for each group ( Yadav et al, 2016 ). By thresholding the association matrices at a range of network densities, we estimated the binary adjacency matrices.…”
Section: Methodsmentioning
confidence: 99%
“…Atrophy in basal ganglia, fronto-temporal regions, occipital lobe and cerebellum had been detected by DBM in PD patients with different stages (Borghammer et al, 2010 ; Zeighami et al, 2015 ) and, recently, DBM also explained the progressive atrophy of PD brains along disease exacerbation (Fereshtehnejad et al, 2017 ). Moreover, structural correlation network (SCN) proposes another sensitive avenue of research to explore brain development and diseases (He et al, 2007 , 2009 ; Zielinski et al, 2010 ; Pereira et al, 2015 ; Yadav et al, 2016 ). Reduced global efficiency and reorganization of network hub in SCN constructed by cortical thickness could be observed in PD patients with mild cognitive impairment (Pereira et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the effect of PD might differ between males and females (Gillies et al, 2014). Although adding age × disease and sex × disease interactions in the linear model did not reveal any significant interactions for the present data (not shown), several imaging studies have suggested that these interactions are non-negligible (Dean et al, 2016;Yadav et al, 2016). The absence of these FIGURE 9 | Correlation with UPDRS-III score in two representative ROIs.…”
Section: Discussionmentioning
confidence: 61%